Effect of different levels of monensin with cold process urea molasses mineral block on rumen fermentation in vitro - DE, DEBASIS; SINGH, G P (The Indian Journal of Animal Sciences, 2014)
Rumen fluid was collected in 2 periods from rumen fistulated cattle adapted with moncnsin (50 mg/d) for 0 (period II) and 21 (period II) days for in vitro microbial fermentation study using wheat straw (WS) and concentrate mixture (3:2, T1), wheat straw and cold process urea molasses mineral block (UMMB) (6: 1; T2), in addition different level of monensin i.e., 35 ppm (T3), 70 ppm (T4), 100 ppm (T5), 150 ppm (T6) and 200 ppm (T7) as substrates. When rumen fluid was used from steer not adapted with monensin, the digestibility of DM, NDF, ADF, and total gas production was significantly lower in all monensin treatments (i.e. T3 T4 T5 T6 and T7) as compared to T1 and T2. Oil the other hand, when rumen liquor was used from monensin adapted steer the digestibility of DM, NDF, ADF, TVFA, and total gas production were not affected but propionate production significantly (P